Sorghum extract: Phytochemical, proximate, and GC-MS analyses - Olayinka O. Ajani (Kemerovo State University, 2021)
Introduction. Sorghum is available cereal seeds of African origin belonging to the Poaceae family. However, its metabolites and proximate composition have not studied well, which led to the under-utilization of this cereal. This research aimed to investigate the classes of phytochemical and proximate compositions of sorghum extract in order to assess its nutraceutical potential for food chemistry and dietary formulations. Study objects and methods. We studied the sorghum seed oil extract obtained with the help of a Soxhlet extractor. Sorghum was purchased in Ota, Nigeria. The bioactive compounds were identified by standard methods of phytochemical screening, the nutritional content was investigated with proximate analysis, and the secondary metabolites in the sorghum extract were determined using gas chromatography – mass spectrometry (GC-MS). Result and discussion. The phytochemical screening showed the presence of steroids, saponins, terpenoids, alkaloids, cardiac glycosides, and quinones in the sorghum extract. The oil yield obtained was 11.00 ± 0.18%. The proximate analysis revealed 5.94% moisture content, 3.05% ash, 0.20% crude fiber, 11.00% fat, 5.54% protein, and 74.27% carbohydrates. The selected physicochemical parameters measured in the sorghum extract included cloud point (0.40°C), specific gravity at 25°C (0.81), and refractive index (1.46). The GC-MS analysis revealed the presence of 9,12-octadecadienoic acid (Z,Z)-, stigmasterol, 8-dodecen-1-ol, acetate, (Z)-, vitamin E, linoleic acid ethyl ester, and 9,12-octadecadienoic acid, methyl ester, which accounted for about 85% in the sorghum composition. Other constituents, presented at lower amounts, included 12-heptadecyn-1-ol, 1H-Imidazole-5-ethanamine, 1-methyl-, and cyclononene. Conclusion. The findings of this study revealed high nutritive potential of sorghum, which make it a rich source of energy for humans and animals.